SKYRIM AS A REPRESENTATION OF THE AMERICAN DOMINANT CULTURE - Rudi Hartanto; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This thesis aims to give pictures of the American values in an American cultural product, Bethesda’s Elder Scroll V: Skyrim. I will use ideology as the concept to show that cultural products contain ideologies or values of the dominant group. The study shows that in the games, traditional American values serve as the standard values of the American dominant group. Furthermore, I show that American values in the video game are the same, although some values are shifting. In conclusion, I find out that Elder Scroll V: Skyrim has all of the American traditional values. The medieval setting of the game somehow shifts some values like material wealth since bloodline status is appreciated. Thus, Elder Scroll V: Skyrim does represent the American society and how it should be.